Sustainability indicator evaluation for biomass feedstock in the biojet supply chain using Fuzzy Delphi method - Hasibuan Sawarni; Nazir Novizar; Kandasani Jayakhrisna (BIO Web of Conferences)
In recent years, the production and consumption of traditional fossil jets have contributed significantly to CO2 emissions. ICAO’s agreement establishes a 2050 net-zero-emission (NZE) goal and outlines a process for states to achieve the accord. Indonesia, like many other countries, is part of international agreements and initiatives aimed at reducing carbon emissions. Producing bio-jet fuel as renewable aviation fuel aligns with these commitments, contributing to global efforts to achieve carbon neutrality. The Indonesian government issued a government instruction through ESDM regarding the target for blending bio-based fuel for aviation fuel 5 by 2025. The purpose of this research is to analyze metrics that need to be evaluated across the biojet fuel supply chain, contributing to a more holistic understanding of sustainability in the context of sustainable aviation fuels (SAF). Potential biomass from Indonesia was evaluated considering technical factors, economic factors, environmental and social factors, and blend limit already approved by ASTM International for the use of bio jet fuels into fossil jet fuel. This research design uses a mixed method, where raw material exploration is carried out using a qualitative approach. The results indicate that 11 validated indicators must be evaluated in designing a sustainable biomass feedstock framework for biojet fuel production in Indonesia. The technical dimension, particularly technology scalability and production volume, is crucial, with significant progress made in bio-jet production platforms like FT and HEFA, which are approved for up to 50% blending with fossil kerosene, while other technologies like microbial sugar-to-jet and ATJ have lower blend approvals.